Does sending honey bee, Apis mellifera (Hymenoptera: Apidae), colonies to lowbush blueberry, Vaccinium angustifolium (Ericaceae), for pollination increase Nosema spp. (Nosematidae) spore loads?. Issue 1 (16th September 2022) - Shaw, J.; Cutler, G.C.; Manning, P.; McCallum, R.S.; Astatkie, T.
Abstract: In the Canadian Maritimes, many beekeepers rent honey bee, Apis mellifera Linnaeus (Hymenoptera: Apidae), hives to growers of lowbush blueberry, Vaccinium angustifolium (Ericaceae), for pollination services. Anecdotally, hives have less vigour following pollination, potentially due to higher Nosema spp. (Nosematidae) spore loads, the microsporidian causing nosemosis. We undertook a study to determine whether sending honey bee hives to lowbush blueberry fields for pollination (blueberry hives) results in higher Nosema spp. spore loads relative to hives remaining in apiaries (home hives). Nosema spp. spore loads were quantified using light microscopy. Nosema apis and Nosema ceranae were differentiated using polymerase chain reaction and sequencing. Nosema spp. spore loads were greatest in April and May and declined to low levels from June to September. Ninety-eight per cent of Nosema detections were positive for N. ceranae . In April, blueberry hives had a lower spore load than home hives did; however, in June, spore loads were significantly higher in blueberry hives. No other differences in Nosema spp. spore loads were observed between hive types. We conclude that Nosema ceranae is the dominant Nosema species in the Canadian Maritimes and that using hives for lowbush blueberry pollination does not appear to influence long-term Nosema spp. spore loads.